Rodzina z czworonogiem. Wybrane przejawy relacji człowiek - pies - Stawarz-Popek, Kinga (Kraków: Akademia im. Andrzeja Frycza Modrzewskiego)
Dogs for millennia operate alongside humans. The presence of these animals, by its universality, usually does not raise research vigilance. Meanwhile, the relationship human - dog could provide an additional resource supporting various forms and areas of human existence. However, to make this possible in a beneficial manner to all concerned parties, it is worth to analyze already existing phenomenons. Especially those related to the functioning of the family.
Keywords: rodzina; relacje; pies; family; dog; relationships